Native and Non-glycosylated Recombinant Single-chain Urokinase-type Plasminogen Activator Are Recognized by Different Receptor Systems on Rat Parenchymal Liver Cells - Kaaden, Marieke E van der; Rijken, Dingeman C; Groeneveld, Eleonore; Berkel, Theo J C van; Kuiper, Johan (Thrombosis and Haemostasis, 1995)
The recognition systems mediating the clearance of glycosylated high molecular weight single-chain urokinase-type plasminogen activator (HMW-scu-PA, produced in human embryonic kidney cells) and recombinant non-glycosylated scu-PA (rscu-PA, produced in E. coli) were analyzed by studying their binding charactaristics to freshly isolated rat parenchymal liver cells.The binding of 125I-HMW-scu-PA at 4° C was calcium-dependent and of high affinity (Kd = 37.6 nM) and could be inhibited by low molecular weight two-chain u-PA (LMW-tcu-PA) and lactose, but not by the low density lipoprotein receptor-related protein (LRP)-associated 39-kDa protein (RAP), rscu-PA or a mutant form lacking amino acids 11-135 (Delta 125-rscu-PA). Removal of the carbohydrate side chain of HMW-scu-PA by treatment with N-glycosidase F, completely reduced the specific binding to the parenchymal cells and strongly reduced its competition with 125I-HMW-scu-PA in cell binding.Recombinant scu-PA also bound with high affinity (Kd= 38.7 nM) to the parenchymal liver cells. The binding of 125I-rscu-PA could be competed for by unlabeled rscu-PA while Delta 125-rscu-PA, LMW-tcu-PA or lactose were ineffective. In contrast to HMW-scu-PA, binding of 125I-rscu-PA could be effectively inhibited by RAP (Ki = 1.1 nM), while also its association and degradation, as determined at 37° C, were inhibited by RAP. Pretreatment of the parenchymal cells with proteinase K supplied further evidence for the involvement of two different receptor systems. The binding of rscu-PA was decreased for 91%, while that of HMW-scu-PA showed a decrease of 51%.It is suggested that native HMW-scu-PA is bound and degraded by the rat parenchymal liver cells via a lectin-like recognition site, while non-glycosylated recombinant scu-PA is bound and degraded by rat parenchymal liver cells via the low density lipoprotein receptor-related protein (LRP). The differences in recognition system for native and recombinant proteins by liver cells suggest that the glycosylation of recombinant proteins, as obtained in mammalian expression systems, can be important for their physiological fate and their pharmacological application.